2013
DOI: 10.1155/2013/545898
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Therapeutics of Berberine Alkaloids

Abstract: Although berberine alkaloids (BAs) are reported to be with broad-spectrum antibacterial and antiviral activities, the interactions among BAs have not been elucidated. In the present study, methicillin-resistant Staphylococcus aureus (MRSA) was chosen as a model organism, and modified broth microdilution was applied for the determination of the fluorescence absorption values to calculate the anti-MRSA activity of BAs. We have initiated four steps to seek the optimal combination of BAs that are (1) determining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…These findings supported the results of other researches that found decreasing S. aureus numbers after treatment with alkaloids (18,21). Although the exposure to crude alkaloid up to 0.5 mg/ml for 2 h resulted in a slight increase of the cell numbers, the decline of sea relative expression was observed.…”
Section: Effect Of Crude Alkaloid To the Cell Number Of Ssupporting
confidence: 91%
“…These findings supported the results of other researches that found decreasing S. aureus numbers after treatment with alkaloids (18,21). Although the exposure to crude alkaloid up to 0.5 mg/ml for 2 h resulted in a slight increase of the cell numbers, the decline of sea relative expression was observed.…”
Section: Effect Of Crude Alkaloid To the Cell Number Of Ssupporting
confidence: 91%
“…Berberine (BBR), an isoquinoline alkaloid, can be isolated from medicinal plants such as Rhizoma coptidis , Scutellaria baicalensis and Phellodendron amurense . Although it is mainly used to treat infectious diseases in traditional medical practice, BBR has recently been explored for lipid-lowering, anti-diabetes, immune modulation, protection of ischemic myocardium, anti-hypertension, anti-arrhythmia and anti-cancer purposes in several studies [1] , [2] .…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of infections with single antibiotics has faced many obstacles. Antibiotic combination therapy is an attractive option for preventing the emergence of resistance and overcoming resistance to single antibiotics [25]. In this study, the results of BBR combined with antibiotics showed that BBR combined with AMI had the best bacteriostatic effect on MRSA and almost had a bactericidal effect.…”
Section: Discussionmentioning
confidence: 76%